Conserving health in early modern culture: Bodies and environments in Italy and England - Storey, Tessa; Cavallo, Sandra (Social Histories of Medicine, 2017)
"Conserving health in early modern culture explores the impact of ideas about healthy living in early modern England and Italy. The attention of medical historians has largely been focussed on the study of illness and medical treatment, yet prevention was one of the cornerstones of early modern medicine. According to Galenic-Hippocratic thought, the preservation of health depended on the careful management of the so-called six 'Non-Naturals': the air one breathed; food and drink; excretions; sleep; movement and rest; and emotions. Drawing on visual, material and textual sources, the contributors show the pervasiveness of the preventive paradigm in early modern culture and society. In particular it becomes apparent that concern for the non-naturals informed lay people's daily lives and routines as well as stimulating innovation in material culture and painting, and influencing discourses in fields as diverse as geology, natural philosophy and religion. At the same time the volume challenges the common assumption that health advice was a uniform and stable body of knowledge, showing instead that models of healthy living were tailored to different genders, age-groups and categories of patients; they also varied over time and depended on the geographical context. In particular, significant differences emerge between what was regarded as beneficial or harmful to health in England and Italy. As well as showing the value of a comparative perspective of study, this interdisciplinary volume will appeal to a wide readership, interested not just in health practices, but in print culture, histories of women, infancy, the environment and of art and material culture."